Quantifying Fire Risks in Pontianak for Future Planning and Development - Affrilyno, Affrilyno; Gultom, Bontor Jumaylinda; Jati, Dian Rahayu; Zhang, Andi (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
Pontianak, a densely populated urban center divided by rivers into three distinct development zones, faces significant fire risk. This research delves into Pontianak's density and accessibility, aiming to craft a resilient city map to effectively combat fire disasters and bolster urban resilience. Its objective is to offer a comprehensive, evidence-based analysis of urban challenges, specifically related to fire risk. Employing a quantitative approach alongside grounded theory analysis, this study investigates how population density and accessibility intertwine within a designated grid. It involves calculating the total building area to establish population distribution and assessing city route accessibility using step-depth space syntax analysis. The results address potential threats, such as the absence of fire stations in certain areas, and underscore the city's weakness, specifically its ineffective accessibility. The output of this study is a gridded map that shows the risk level of each area in Pontianak, raising awareness among citizens and encouraging proactive measures, such as equipping homes with fire extinguishers and adopting fire-resistant materials during construction.